If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = 2v + -3 Reorder the terms: -9 = -3 + 2v Solving -9 = -3 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. -9 + -2v = -3 + 2v + -2v Combine like terms: 2v + -2v = 0 -9 + -2v = -3 + 0 -9 + -2v = -3 Add '9' to each side of the equation. -9 + 9 + -2v = -3 + 9 Combine like terms: -9 + 9 = 0 0 + -2v = -3 + 9 -2v = -3 + 9 Combine like terms: -3 + 9 = 6 -2v = 6 Divide each side by '-2'. v = -3 Simplifying v = -3
| 6x-(2x-3)=4x+5 | | x^4+4x^3+12x^2+12x-9=0 | | X/3+6=11 | | -5s=-1.25 | | 13x+19y=-17 | | 6x+75=9x+93 | | -2+8(x-5)=13x+6-5x | | -3(y-0.5)=0.5 | | -8.978=1.34t | | 3x(2-4)=24 | | -0.67(x+1)=6 | | 4(a-5)+6=2(a-6) | | 8x-3=7(x+5)+4 | | -5s=1.25 | | 3/4x-1=7/5 | | 9x-2=6x+43 | | -3=5(z+7) | | 3X+8Y=30 | | 24=-8y | | 4x^2-19x+24=-2x+9 | | 4x^2-16x+24=-2x+9 | | 12(r-2)=0 | | (8r-64)/4 | | 8r-64/4 | | (X^3+9x^2+7x-24)/(x-2) | | (7/4)x=56 | | 9/1-27/7 | | .5=.5555 | | 12x+3+4x=48 | | 4ax+5ab= | | 6x^5+10x^4-56x^3=0 | | 36/7+X=9 |